On S-Subcontinuous multifunctions (Journal of the College of Basic Education, 2023)
In this paper we introduce a new concept, namely the s-subcontinuity for multifunction as a generalization of subcontinuity. We characterize s-compact preserving multifunctions in terms of s-subcontinuity. Conditions implying upper s-semi continuity for multifunction are derived. Several new characterizations for upper s- semi-continuity and lower s- semi continuity are obtained using filterbasis. Furthermore we obtain some results on multifunction with s-closed graphs.